2013
DOI: 10.1890/12-1444.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative gradient of subsidies reveals a threshold in community‐level trophic cascades

Abstract: Evidence varies on how subsidies affect trophic cascades within recipient food webs. This could be due to complex nonlinearities being masked by single-level manipulations (presence/absence) of subsidies in past studies. We predicted that trophic cascade strength would increase nonlinearly across a gradient of subsidies. We set out to reveal these complex, nonlinear relationships through manipulating a quantitative gradient of detrital subsidies to lake benthic food webs along with the presence/absence of trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Trophic cascades, a potential consequence of subsidies, vary in strength and are commonly thought to be influenced by consumer body size [44], quantity of subsidy input [45], general system productivity, diversity of primary producers [46], and predator traits [47,48], as well as habitat heterogeneity [8]. In addition, physical and ecological attributes of each ecosystem (aquatic or terrestrial) can give insight into potential trophic cascades following a particular amount of allochthonous resources they receive [45].…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Trophic cascades, a potential consequence of subsidies, vary in strength and are commonly thought to be influenced by consumer body size [44], quantity of subsidy input [45], general system productivity, diversity of primary producers [46], and predator traits [47,48], as well as habitat heterogeneity [8]. In addition, physical and ecological attributes of each ecosystem (aquatic or terrestrial) can give insight into potential trophic cascades following a particular amount of allochthonous resources they receive [45].…”
Section: Research Articlementioning
confidence: 99%
“…In addition, physical and ecological attributes of each ecosystem (aquatic or terrestrial) can give insight into potential trophic cascades following a particular amount of allochthonous resources they receive [45]. Generally, aquatic ecosystems experience stronger trophic cascades than in terrestrial systems [49][50][51] with several reasons, including their low level and concave structure naturally attracting a greater rate of input, in comparison with mountain areas or even flat terrestrial areas [47].…”
Section: Research Articlementioning
confidence: 99%
“…This has made it difficult to make quantitative predictions of the subsidy effects beyond the studies showing the effects in a binary comparison. In one exception to the aforementioned, Klemmer and Richardson () recently demonstrated that the trophic cascades in lakes only occurred at low subsidy levels of alder leaf inputs, disappearing as subsidies increased, probably through changes in the density of intermediate predators and/or the proportions of edible/inedible preys with subsidy gradients (i.e. nonlinearity of community‐level responses to the subsidies).…”
Section: Current Understanding Of Cross‐ecosystem Flowsmentioning
confidence: 99%
“…Manipulation of input rates of periodical cicadas to pond mesocosms demonstrated a positive response of biofilms and consumers along the input gradient (Nowlin et al 2007). Klemmer and Richardson (2013) created a gradient of leaf litter abundance in cages in a lake with or without trout present and demonstrated a positive and generally asymptotic response in the numbers of detritivores. Jones and Lennon (2015) created an experimental gradient in the concentrations of dissolved organic carbon (DOC) in a series of ponds, which led to increased bacterial productivity along that concentration gradient, although overall system productivity was hump-shaped due to the light attenuation effect of colored DOC and reduced primary productivity.…”
Section: Quantitative Effects Of Experimental Manipulationsmentioning
confidence: 99%